JOURNAL OF GOVERNMENT & POLITICS : Pick Your Own Rubbish : An Analysis Of Target Group Compliance In Public Policy Implementation - Tutik Rachmawati , Dhia Kalila Rinjany (FISIPOL UMY, 2016)
The purpose of this research is to analyse the implementation of Local Government Act Bandung Municipality Number 11/2005 about Orerliness, Cleanliness and Fineness of Bandung City.